Uyghur–Chinese Adult Bilinguals’ Construal of Voluntary Motion Events - Tusun, Alimujiang (Frontiers in Psychology, 2022)
The study examined the implications of Talmy’s (2000) motion event typology and Slobin’s (1996, 2006) thinking-for-speaking hypothesis for the context of Uyghur-Chinese early successive bilingualism. Uyghur and Chinese represent genetically distant languages (Turkic vs. Sino-Tibetan) that nonetheless share important framing properties in the motion domain, i.e., verb-framing. This study thus aimed to establish how this structural overlap would inform bilingual speakers’ construal of motion events. Additionally, it sought to offer an ‘end state’ perspective to a previous study on Uyghur-Chinese child bilinguals (Tusun, 2019) and to shed light on issues around the longevity of crosslinguistic influence (cf. Serratrice, 2020). Thirty adult Uyghur-Chinese early successive bilinguals were invited to describe a set of voluntary motion events (e.g., ‘a man runs across the road’). Their verbalisations, alongside those from 24 monolingual Uyghur and 12 monolingual Chinese speakers were systematically analysed with regard to the kind of linguistic devices used to encode key components of motion (main verb vs. other devices), the frequency with which the components are expressed together (Path+Manner) or separately (Path or Manner) and how they are syntactically packaged. The findings show that the bilinguals’ thinking-for-speaking patterns are largely language-specific, with little crosslinguistic influence. A comparison of our findings with Tusun (2019) revealed no development either in the analysed aspects of motion descriptions or in patterns of crosslinguistic influence. As such, it lends support to accounts that propose crosslinguistic influence to be a developmental phenomenon.